Water-resistant and pressure-resistant energized solid waste curing material as well as preparation method and application of water-resistant and pressure-resistant energized solid waste curing material
By preparing water-resistant and pressure-resistant empowered solid waste solidification materials and using a multi-functional group chelating system to capture heavy metal ions in lithium slag, the problem of heavy metal migration pollution in the resource utilization of lithium slag is solved, and the efficient solidification and environmental safety of the material are achieved.
Patent Information
- Application Number
- CN202511277346.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-09
- Publication Date
- 2025-10-10
- Estimated Expiration
- 2045-09-09
AI Technical Summary
The resource utilization rate of lithium slag is low, and the migration pollution of heavy metal ions is serious. Existing chelating agents mostly target single metals and lack the ability to synergistically fix multiple ions. Soil solidifiers fail to solve the problem of long-term sealing of harmful ions.
Water-resistant and pressure-resistant solid waste solidification materials are prepared by esterification and emulsification processes using components such as polyglycerol fatty acid esters, acetic acid, fatty alcohol polyoxyethylene ether, polyvinyl alcohol, sodium lignin sulfonate and emulsified paraffin. A multi-functional chelating system is formed to capture heavy metal ions in lithium slag and form stable chelates, blocking the leaching path of harmful substances.
The multi-ion synergistic fixation of heavy metal ions in lithium slag is achieved, which improves the material's water and pressure resistance and environmental safety, ensures the material's long-term stability in the natural environment, and avoids oxide deliquescence and secondary pollution.
Smart Images

Figure CN120755161A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium slag energy-saving and environmental protection technology, and in particular to a water-resistant and pressure-resistant energized solid waste solidification material, and a preparation method and application thereof. Background Art
[0002] The rapid rise of the new energy sector has spurred the rapid development of the lithium salt industry, but this has also generated significant amounts of lithium slag, leading to an increasingly problematic storage problem. Currently, the low utilization rate and limited application scope of lithium slag resources make large-scale disposal difficult, a major pain point for the industry.
[0003] Lithium slag has a yellowish-brown appearance and becomes powdery after drying. It has a large specific surface area and a porous structure. After high-temperature roasting, its chemical properties are stable, and its main components are SiO2, Al2O3, CaO, etc. In recent years, the research on the soilification of lithium slag has become a key direction, and exploration has been carried out on issues such as heavy metal pollution, nutritional imbalance, pH adjustment, microbial activity, and long-term stability, aiming to open up new ways for the ecological return of lithium slag to large-scale disposal. However, existing chelating agents are mostly targeted at single metals (such as Cr 6+ ), lacks the ability to synergistically fix multiple ions; soil solidifier (CJ / T 486-2015) fails to solve the problem of long-term sealing of harmful ions.
[0004] This new "soil-solidifying" water- and pressure-resistant material is made from a variety of uniquely engineered materials through a specialized process. Rich in active ingredients, it reacts with soil and slag particles to initiate a series of physical and chemical reactions. This process, called modification, reconnection, and solidification, densifies the mixture, resulting in robust, compressive-resistant, and water-resistant engineering properties. Therefore, designing new "soil-solidifying" water- and pressure-resistant materials is a pressing challenge. Summary of the Invention
[0005] The present invention provides a water-resistant and pressure-resistant energized solid waste solidification material and a preparation method and application thereof, so as to overcome the problems of heavy metal ion migration pollution and insufficient resource utilization intensity in lithium slag solid waste in the prior art.
[0006] In order to achieve the above-mentioned purpose, the technical solution of the embodiment of the present invention is:
[0007] The first aspect of the present invention provides a water-resistant and pressure-resistant energized solid waste solidification material, which is prepared by including the following components in percentage by weight:
[0008] Polyglycerol fatty acid ester 5-15%, acetic acid 10-20%, fatty alcohol polyoxyethylene ether 35-50%, polyvinyl alcohol 3-5%, sodium lignin sulfonate 3-5%, emulsified paraffin 15-30%.
[0009] Preferably in combination with the second aspect, the preparation is made by including the following components with the following mass percentage: polyglycerol fatty acid ester 5%, acetic acid 20%, fatty alcohol polyoxyethylene ether 45%, polyvinyl alcohol 3%, sodium lignosulfonate 4%, emulsified paraffin wax 23%.
[0010] The second aspect of the present application provides a method for preparing the water-resistant and compression-resistant enabled solid waste solidification material of the first aspect, comprising:
[0011] Esterification is performed on the polyglycerol fatty acid ester and acetic acid, and the acid value of the solution during the reaction is controlled within a preset acid value threshold range, after which a first reaction solution is obtained;
[0012] A basic solution is slowly added dropwise to the first reaction solution, and after the pH of the solution is adjusted to be alkaline, a second reaction solution is obtained;
[0013] Fatty alcohol polyoxyethylene ether, polyvinyl alcohol solution, and sodium lignosulfonate solution are sequentially added to the second reaction solution, and after reaction, a mixed solution is obtained;
[0014] After the mixed solution is cooled to a preset temperature range, emulsified paraffin wax is added for reaction, and a water-resistant and compression-resistant enabled solid waste solidification material is obtained after cooling.
[0015] Preferably in combination with the second aspect, the temperature range of the esterification reaction is 80-110 ℃, and the reaction time is 1-3 h.
[0016] Preferably in combination with the second aspect, the preset acid value threshold range is 35-50 mg KOH / g.
[0017] Preferably in combination with the second aspect, the basic solution includes one or more of sodium bicarbonate and sodium hydroxide.
[0018] Preferably in combination with the second aspect, the reaction temperature of the fatty alcohol polyoxyethylene ether is 65-75 ℃, and the reaction time is 20 min.
[0019] Preferably in combination with the second aspect, the pre-dissolution temperature of the polyvinyl alcohol solution is 85 ℃, and the solid-liquid ratio is 1:15; the pre-dissolution temperature of the sodium lignosulfonate solution is 40-50 ℃, and the solid-liquid ratio is 1:5.
[0020] The third aspect of the present application provides an application of the water-resistant and compression-resistant enabled solid waste solidification material of any one of the first aspect or the water-resistant and compression-resistant enabled solid waste solidification material prepared by any one of the methods of the second aspect in non-burned building materials.
[0021] The fourth aspect of the present application provides a non-burned brick comprising the water-resistant and compression-resistant enabled solid waste solidification material of any one of the first aspect or the water-resistant and compression-resistant enabled solid waste solidification material prepared by any one of the methods of the second aspect.
[0022] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present invention include at least:
[0023] The water-resistant and pressure-resistant solid waste solidification material provided by the present invention can give the solidification material excellent reactivity based on the active chemical bonds and organic functional groups rich in the molecular structure of the contained compounds through the polymerization of the compounds contained therein, thereby achieving the effect of accurately capturing free metal particles and non-metallic ions in lithium slag and causing a chelating reaction. Specifically, the acetylated product generated by the esterification reaction of polyglycerol fatty acid ester and acetic acid can serve as the core skeleton, and can form a stable coordination bond with heavy metal ions (such as thallium and beryllium) through its electron-rich carboxyl group; the ether bond of fatty alcohol polyoxyethylene ether cooperates with the phenolic hydroxyl group of sodium lignin sulfonate to capture fluoride and manganese ions through hydrogen bond-coordination dual-mode action; the long alkane chain of emulsified paraffin can directionally wrap the chelate and form a hydrophobic barrier, completely blocking the leaching path of harmful substances. The above components can cooperate to effectively capture free metal particles and non-metallic ions in lithium slag and cause a chelating reaction, achieving a multi-ion synergistic fixation effect; at the same time, its molecular structure The hydrogen in the structure is easily replaced by halogen elements such as fluorine, oxygen atoms and halogen elements are easily combined with thallium in a highly efficient manner, and carbon atoms and halogen elements are easily reacted with beryllium to generate covalent carbides, oxides, and halides (such as fluorocarbons, beryllium carbide, alkyl thallium, halogenated organic thallium, etc.) with organic chain structures to generate compounds; in addition, the materials contained in the solidifying material are mostly hydrophobic and can exist stably for a long time in the natural environment, effectively avoiding the problem of thallium oxide, thallium hydroxide and conventional salts being prone to deliquescence, and will not dissolve in water to cause secondary pollution and harm, which significantly improves the environmental safety and material stability in the solid waste treatment process.
[0024] The present invention fundamentally solves the difficult problems of heavy metal ion migration pollution and insufficient resource utilization intensity in solid waste (lithium slag, coal gangue, phosphogypsum, etc.). The constructed "chelation-encapsulation-hydrophobic" triple stabilization mechanism, combined with a four-stage organic polymerization process, provides technical support for scalable application in the construction of "zero-waste cities". BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a SEM image of Example 3 provided by the present invention;
[0026] Figure 2 FT-IR diagram of Example 3 provided by the present invention;
[0027] Figure 3 H of Example 3 provided by the present invention 1 -NMR spectrum;
[0028] Figure 4 C of Example 3 provided by the present invention 13 -NMR spectrum;
[0029] Figure 5 The solid waste mechanism diagram of the solidified agent provided by the present application for treating lithium residue is shown. DETAILED DESCRIPTION
[0030] In order to make the objects, technical solutions and advantages of the present application clearer, the present application will be further described in detail below with reference to the drawings, and the described embodiments should not be regarded as limiting the present application. All other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.
[0031] In the following description, “some embodiments” are related to a subset of all possible embodiments, but it can be understood that “some embodiments” can be the same subset or different subsets of all possible embodiments, and can be combined with each other without conflict. Unless otherwise defined, all technical and scientific terms used in the embodiments of the present application have the same meanings as those commonly understood by those skilled in the technical field to which the embodiments of the present application belong. The terms used in the embodiments of the present application are only for the purpose of describing the embodiments of the present application, and are not intended to limit the present application.
[0032] In the following description of the embodiments of the present application, the terms “include”, “contain”, “have” and “comprise” and the like are all open terms, that is, they mean to include but not limited to.
[0033] It should be noted that all raw materials / reagents in the embodiments of the present application can be purchased on the market or prepared according to conventional methods well known to those skilled in the art; the term “and / or” in the embodiments of the present application is only used to describe the association relationship of the associated objects, which means that there can be three relationships, for example, A and / or B means that there are three cases of A alone, B alone and A and B together, wherein A and B can be singular or plural, and the character “ / ” generally represents an “or” relationship between the associated objects before and after it.
[0034] In the following description of the embodiments of the present application, the term “at least one” means one or more, and “multiple” means two or more. “At least one of the following” or similar expressions means any combination of these items, including any combination of single item or multiple items. For example, “at least one of a, b or c”, or “at least one of a, b and c”, can mean a, b, c, a-b (i.e. a and b), a-c, b-c, or a-b-c, wherein a, b and c can be single or multiple.
[0035] Those skilled in the art should understand that in the following description of the embodiments of the present invention, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present invention.
[0036] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The singular forms "a", "an" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates otherwise.
[0037] It will be understood by those skilled in the art that the numerical ranges in the embodiments of the present invention are to be understood as also specifically disclosing each intermediate value between the upper and lower limits of the ranges. Each smaller range between any stated value and intermediate value in the stated range, as well as any other stated value or intermediate value in the stated range, is also encompassed by the present invention. The upper and lower limits of these smaller ranges may independently be included or excluded in the range.
[0038] Unless otherwise indicated, the technical / scientific terms used herein have the same meanings as those commonly understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the embodiments or test examples of the present invention. All documents mentioned in this specification are generally incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0039] It should be noted that all raw materials and / or reagents in the examples of the present invention are purchased on the market or prepared according to conventional methods well known to those skilled in the art.
[0040] In a first aspect, an embodiment of the present invention provides a water-resistant and pressure-resistant energized solid waste solidification material, which is prepared by including the following components in percentage by weight:
[0041] Polyglycerol fatty acid ester 5-15%, acetic acid 10-20%, fatty alcohol polyoxyethylene ether 35-50%, polyvinyl alcohol 3-5%, sodium lignin sulfonate 3-5%, emulsified paraffin 15-30%.
[0042] In a specific embodiment, the composition is prepared by including the following components in percentage by weight: 5% polyglycerol fatty acid ester, 20% acetic acid, 45% fatty alcohol polyoxyethylene ether, 3% polyvinyl alcohol, 4% sodium lignin sulfonate, and 23% emulsified paraffin.
[0043] It should be noted that polyglycerol fatty acid esters and fatty alcohol polyoxyethylene ethers are combined as surfactants in the components, which jointly build a powerful emulsification, wetting, penetration and dispersion system, ensuring that the hydrophobic paraffin can be evenly and stably dispersed, and effectively infiltrate and wrap the solid waste particles.
[0044] PVA and sodium lignin sulfonate serve as bonding skeletons in the components, providing the main mechanical strength and structural integrity, bonding and fixing the solid waste particles and functional components.
[0045] Emulsified paraffin acts as a hydrophobic barrier in the component to provide core waterproofing properties, and its effect relies on surfactants to evenly disperse and spread it.
[0046] Acetic acid provides a suitable acidic chemical environment for the entire system, ensuring the functions of key components and possibly neutralizing alkaline interferents in solid waste.
[0047] Sodium lignin sulfonate plays an important role in dispersing solid waste particles, assisting in bonding enhancement, and improving processability.
[0048] The water-resistant and pressure-resistant solid waste solidification material provided by the present invention can give the solidification material excellent reactivity based on the active chemical bonds and organic functional groups rich in the molecular structure of the contained compounds through the polymerization of the compounds contained therein, thereby achieving the effect of accurately capturing free metal particles and non-metallic ions in lithium slag and causing a chelating reaction. Specifically, the acetylated product generated by the esterification reaction of polyglycerol fatty acid ester and acetic acid can serve as the core skeleton, and can form a stable coordination bond with heavy metal ions (such as thallium and beryllium) through its electron-rich carboxyl group; the ether bond of fatty alcohol polyoxyethylene ether cooperates with the phenolic hydroxyl group of sodium lignin sulfonate to capture fluoride and manganese ions through hydrogen bond-coordination dual-mode action; the long alkane chain of emulsified paraffin can directionally wrap the chelate and form a hydrophobic barrier, completely blocking the leaching path of harmful substances. The above components can cooperate to effectively capture free metal particles and non-metallic ions in lithium slag and cause a chelating reaction, achieving a multi-ion synergistic fixation effect; at the same time, its molecular structure The hydrogen in the structure is easily replaced by halogen elements such as fluorine, oxygen atoms and halogen elements are easily combined with thallium in a highly efficient manner, and carbon atoms and halogen elements are easily reacted with beryllium to generate covalent carbides, oxides, and halides (such as fluorocarbons, beryllium carbide, alkyl thallium, halogenated organic thallium, etc.) with organic chain structures to generate compounds; in addition, the materials contained in the solidifying material are mostly hydrophobic and can exist stably for a long time in the natural environment, effectively avoiding the problem of thallium oxide, thallium hydroxide and conventional salts being prone to deliquescence, and will not dissolve in water to cause secondary pollution and harm, which significantly improves the environmental safety and material stability in the solid waste treatment process.
[0049] In a second aspect, an embodiment of the present invention provides a method for preparing a water-resistant and pressure-resistant energized solid waste solidification material, the preparation method comprising:
[0050] esterifying polyglycerol fatty acid ester and acetic acid, and controlling the acid value of the solution in the reaction process within a preset acid value threshold range, and then obtaining a first reaction solution;
[0051] slowly adding a basic solution to the first reaction solution, adjusting the pH of the solution to be alkaline, and then obtaining a second reaction solution;
[0052] adding fatty alcohol polyoxyethylene ether, polyvinyl alcohol solution, and sodium lignosulfonate solution to the second reaction solution in sequence, and then obtaining a mixed solution after reaction;
[0053] cooling the mixed solution to a preset temperature range, adding emulsified paraffin for reaction, and then cooling to obtain a water-resistant and pressure-resistant enabled solid waste solidification material.
[0054] In specific embodiments, the temperature range of the esterification reaction is preferably 80-110°C, and the reaction time is preferably 1-3 hours.
[0055] In the present application, if the esterification temperature is lower than 80°C, the esterification reaction rate will slow down significantly, resulting in incomplete reaction of polyglycerol fatty acid ester and acetic acid. The residual unreacted raw materials will cause the effective active ingredients in the first reaction solution to be insufficient. This will directly affect the subsequent neutralization reaction with the alkaline solution and the synergistic effect of various additives, ultimately leading to a decrease in the crosslinking density of the solidification material and a decrease in water resistance and compressive strength. If the temperature is higher than 110°C, on the one hand, it will accelerate the volatilization loss of acetic acid, disrupting the material ratio balance of the reaction system; on the other hand, it may cause thermal decomposition or oxidation side reactions of polyglycerol fatty acid ester, generating unstable impurity components. These impurities will interfere with the efficiency of the subsequent chelation reaction, leading to a decrease in the stability of the molecular structure of the solidification material, weakening the compressive performance, and significantly reducing the ability to capture metal ions in lithium slag.
[0056] If the reaction time is less than 1 hour, the esterification reaction has not been fully carried out, and the amount of ester bonds generated in the system is insufficient, which will cause the functional group activity of the first reaction solution to be low. This will affect the binding efficiency of the subsequent components such as fatty alcohol polyoxyethylene ether and polyvinyl alcohol, making the network structure of the solidification material loose, the water resistance poor, and it difficult to form a firm overall structure when solidifying lithium slag, resulting in insufficient compressive strength.
[0057] If the reaction time exceeds 3 hours, excessive reaction will cause excessive crosslinking of ester bonds in the system, causing the viscosity of the first reaction solution to abnormally increase. This will affect the uniformity when adjusting the pH value of the subsequent alkaline solution, as well as the dispersion effect of various additives, ultimately causing uneven distribution of components in the solidification material, and obvious differences in local water resistance and compressive performance, resulting in a decrease in overall performance stability.
[0058] In specific embodiments, the preset acid value threshold range is preferably 35-50 mg KOH / g.
[0059] In the present invention, an excessively high acid value means that excessive amounts of unreacted acetic acid or acidic intermediates remain in the system, resulting in overly acidic properties in the first reaction solution. The subsequent addition of an alkaline solution to adjust the pH requires more alkali, which not only increases costs but can also release significant amounts of heat due to localized, intense neutralization reactions, disrupting system stability (e.g., causing thermal decomposition of some components) and leading to uneven dispersion of subsequent additives (e.g., polyvinyl alcohol and sodium lignin sulfonate). Furthermore, excess acidic substances can react with subsequently added fatty alcohol polyoxyethylene ethers and emulsified paraffin (e.g., hydrolysis of the emulsifier and acidolysis of the wax), disrupting the orderly arrangement of the hydrophobic groups. This results in an incomplete hydrophobic network in the final material, allowing water molecules to easily penetrate and significantly reducing water resistance.
[0060] In the present invention, a too low acid value indicates excessive esterification, resulting in excessive ester bonds between the polyglycerol fatty acid ester and acetic acid, and even excessive intermolecular cross-linking, which causes a sudden increase in the viscosity of the first reaction liquid. This can make it difficult to evenly diffuse the subsequent alkaline solution, leading to localized deviations in pH adjustment, and preventing additives such as fatty alcohol polyoxyethylene ether from fully dissolving and dispersing, resulting in an uneven composition of the final material.
[0061] In a specific embodiment, the alkaline solution is preferably at least one of sodium bicarbonate and sodium hydroxide.
[0062] In a specific embodiment, the reaction temperature of the fatty alcohol polyoxyethylene ether is preferably 65-75° C., and the reaction time is preferably 20 min.
[0063] In the present invention, if the temperature is below 65°C, the molecular motion activity of the fatty alcohol polyoxyethylene ether is insufficient, making it difficult to fully diffuse in the second reaction liquid and form stable intermolecular forces with the ester products in the system. This results in its emulsification and dispersing functions not being fully exerted, making it difficult for subsequently added components such as polyvinyl alcohol and sodium lignin sulfonate to be evenly dispersed. The final material is prone to local component enrichment or vacancies, and the uniformity of water resistance and compressive strength is reduced. If the temperature is above 75°C, the ether bonds of the fatty alcohol polyoxyethylene ether may undergo thermal degradation, resulting in a change in its hydrophilic-lipophilic balance and a significant weakening of its emulsification ability. At the same time, high temperatures may accelerate the oxidation reaction of some components in the system, generating polar impurities, disrupting the orderly arrangement of hydrophobic groups, and reducing the material's water resistance. In addition, excessive thermal motion can also affect the stability of the intermolecular cross-linking structure, resulting in a decrease in the material's compressive strength.
[0064] In the present invention, if the reaction time is shorter than 20 minutes, the fatty alcohol polyoxyethylene ether fails to fully interact with the system and cannot form a stable micelle structure in the liquid phase. This makes it difficult for subsequently added polymer chains such as polyvinyl alcohol and sodium lignin sulfonate to achieve uniform dispersion through their bridging effect. This can lead to the formation of localized weak areas within the material, which are prone to stress concentration when subjected to stress, reducing compressive strength. Furthermore, the uneven distribution of hydrophobic components can cause localized defects in the material's water resistance, making it prone to water penetration. If the reaction time exceeds 20 minutes, the excessively long reaction time can cause the fatty alcohol polyoxyethylene ether to excessively aggregate in the system, forming large micelles, which in turn disrupts the system's dispersion equilibrium. This can lead to an uneven microstructure after the material solidifies, with some areas becoming more brittle due to excessive hydrophobic components, while others becoming less water-resistant due to exposed hydrophilic components. This reduces overall performance stability and prevents the desired water and pressure resistance from being achieved.
[0065] In a specific embodiment, the pre-dissolution temperature of the polyvinyl alcohol solution is preferably 85° C., and the solid-liquid ratio is preferably 1:15.
[0066] In a specific embodiment, the pre-dissolution temperature of the sodium lignin sulfonate solution is preferably 40-50° C., and the solid-liquid ratio is preferably 1:5.
[0067] In a third aspect, an embodiment of the present invention provides an application of the water-resistant and pressure-resistant solid waste solidification material described in any one of the first aspects or the water-resistant and pressure-resistant solid waste solidification material prepared by any one of the methods described in the second aspect in fire-free building materials.
[0068] In a fourth aspect, an embodiment of the present invention provides a fire-free brick comprising any of the water-resistant and pressure-resistant energy-empowered solid waste solidification materials described in the first aspect or the water-resistant and pressure-resistant energy-empowered solid waste solidification materials prepared by any of the methods described in the second aspect.
[0069] The technical method of the present invention will be further described below with reference to specific embodiments.
[0070] The present invention also provides an application method of the water-resistant and pressure-resistant energized solid waste solidification material, which is specifically as follows:
[0071] Unburned brick process: 80% solid waste raw materials + 0.2%-0.5% curing agent + 0.3% quicklime → mixed and pressed → natural curing (no sintering required).
[0072] Road base: solid waste replacement gravel + curing agent 0.3% → mixing and paving → compaction (meeting CJJ / T 286-2018 standard).
[0073] It should be noted that the above-mentioned solid waste raw materials include but are not limited to lithium slag, etc.
[0074] Example 1
[0075] A method for preparing a new water-resistant and pressure-resistant solid waste solidification material, the method comprising the following steps:
[0076] (1) Raw material ratio (mass percentage): polyglycerol fatty acid ester: 8%, acetic acid: 15%, fatty alcohol polyoxyethylene ether: 40%, polyvinyl alcohol: 4%, sodium lignin sulfonate: 5%, emulsified paraffin: 28%.
[0077] (2) Preparation steps:
[0078] Stage 1: Esterification reaction: polyglycerol fatty acid ester and acetic acid were added to the reactor and the temperature was slowly raised to 105 °C. The reaction was kept at this temperature for 2.5 h. The endpoint was controlled by reducing the acid value from 180 mg KOH / g to 45 mg KOH / g.
[0079] Stage 2: Neutralize the system, cool to 75 °C, slowly add 10% NaHCO3 solution, and adjust the pH to 7.0.
[0080] Stage 3: Construct an emulsified system, add fatty alcohol polyoxyethylene ether (75 ℃, stirring for 20 min), add the polyvinyl alcohol solution pre-dissolved at 85 ℃ (solid-liquid ratio 1:15) into the system, and then add the sodium lignin sulfonate solution pre-dissolved at 40 ℃ (solid-liquid ratio 1:5) into the system.
[0081] Stage 4: Emulsified paraffin was integrated, the temperature was lowered to 55 °C, emulsified paraffin was added dropwise, and the mixture was stirred at a constant temperature for 25 min. A light yellow viscous liquid was obtained after cooling.
[0082] (3) Application effect:
[0083] Table 1 Application effect of Example 1
[0084]
[0085] Example 2
[0086] (1) Raw material ratio (mass percentage): polyglycerol fatty acid ester: 12%, acetic acid: 18%, fatty alcohol polyoxyethylene ether: 35%, polyvinyl alcohol: 5%, sodium lignin sulfonate: 3%, emulsified paraffin: 27%.
[0087] (2) Innovations in preparation process:
[0088] Stage 1: Esterification enhancement: polyglycerol fatty acid ester and acetic acid were added to the reactor and the temperature was slowly raised to 115 °C for 2 h. The endpoint was controlled to reduce the acid value to 35 mg KOH / g.
[0089] Phase 2: Neutralization optimization, cooling to 80 °C, and using 10% NaOH solution to adjust the pH to 7.2 (avoid CO2 bubbles).
[0090] Stage 3: Construct an emulsified system. Add 0.1% defoamer (to prevent foaming during stirring) to the polyvinyl alcohol solution pre-dissolved at 85°C (solid-liquid ratio 1:15) and add it to the system. Add fatty alcohol polyoxyethylene ether in two portions (first 70%, then 30%) and stir at 75°C for 20 minutes. Then, add the sodium lignin sulfonate solution pre-dissolved at 40°C (solid-liquid ratio 1:5) to the system.
[0091] Stage 4: Emulsified paraffin was integrated, cooled to 58 °C, and emulsified paraffin was slowly injected (2 mL / min), and ultrasonic dispersion (40 kHz) was performed for 15 min. The mixture was aged for 24 h and cooled to obtain a light yellow viscous liquid.
[0092] (3) Application effect:
[0093] Table 2 Application effect of Example 2
[0094]
[0095] Example 3
[0096] (1) Raw material ratio (mass percentage): polyglycerol fatty acid ester: 5%, acetic acid: 20%, fatty alcohol polyoxyethylene ether: 45%, polyvinyl alcohol: 3%, sodium lignin sulfonate: 4%, emulsified paraffin: 23%.
[0097] (2) Process adjustment:
[0098] Stage 1: Low-temperature esterification: Polyglycerol fatty acid ester and acetic acid are added to a reactor equipped with a condenser reflux device and the temperature is slowly raised to 100°C and reacted for 3 hours (to protect heat-sensitive components). The endpoint is controlled by reducing the acid value to 50 mg KOH / g.
[0099] Phase 2: The system is precisely neutralized, and the pH online monitor is used to control the NaHCO3 addition rate.
[0100] Stage 3: Construct a low-temperature emulsification system. Stir the fatty alcohol polyoxyethylene ether at 65°C (to protect the activity of the ether bond) and maintain for 20 minutes. Dissolve and add the polyvinyl alcohol (solid-liquid ratio 1:5) solution pre-dissolved at 85°C. Stir the reaction system at a constant temperature of 70°C for 25 minutes (to prevent PVA precipitation). Then slowly add the sodium lignin sulfonate (solid-liquid ratio 1:5) solution pre-dissolved at 40°C and stir for 15 minutes until homogeneous.
[0101] Stage 4: Emulsified paraffin was integrated, cooled to 52 °C, and emulsified paraffin was added in three batches (8 min interval between each batch). Each batch was simultaneously ultrasonically dispersed (40 kHz) for 15 min, then matured for 24 h and cooled to obtain a light yellow viscous liquid.
[0102] (3) Application effect:
[0103] Table 3 Application effect of Example 3
[0104]
[0105] Example 4
[0106] (1) Raw material ratio (mass percentage): polyglycerol fatty acid ester: 15%, acetic acid: 10%, fatty alcohol polyoxyethylene ether: 50%, polyvinyl alcohol: 4%, sodium lignin sulfonate: 5%, emulsified paraffin: 16%.
[0107] (2) Process adjustment:
[0108] Stage 1: Polyglycerol fatty acid ester and acetic acid were added to a reactor equipped with a condenser reflux device for a staged esterification reaction. The pre-reaction was performed at 80 °C for 1 h (activation of hydroxyl groups) and the main reaction was performed at 110 °C for 1.5 h. The endpoint was controlled by reducing the acid value to 50 mg KOH / g.
[0109] Phase 2: System neutralization and strengthening, using the double alkali method (first adjust NaHCO3 to pH = 5.0 to eliminate strong acidity, then use NaOH to adjust to pH = 7.0).
[0110] Stage 3: Construct an emulsified system, add fatty alcohol polyoxyethylene ether (stir at 75 °C for 20 min), add 0.5% glycerol when polyvinyl alcohol is pre-dissolved at 85 °C (to accelerate hydration), and then add sodium lignin sulfonate solution pre-dissolved at 50 °C (solid-liquid ratio 1:5) into the system.
[0111] Stage 4: Emulsified paraffin was integrated, cooled to 60 °C, and emulsified paraffin was added in three batches (8 min interval), and each batch was ultrasonically dispersed (40 kHz) for 15 min, then matured for 24 h and cooled to obtain a light yellow viscous liquid.
[0112] (3) Application effect:
[0113] Table 4 Application effect of Example 4
[0114]
[0115] According to the application effects of the above-mentioned Examples 1-4, Example 1, as the basic solution (initial effect), includes: lithium slag treatment: using "0.3% curing agent + 0.3% quicklime", the harmful substance reduction multiples are relatively low (3.51 times for fluorine, 2.80 times for thallium, 1200 times for beryllium, and 1800 times for manganese), the compressive strength of the unfired bricks is ≥20 MPa, and both environmental protection and engineering performance are at the starting level; phosphogypsum treatment: "0.3L / m³ curing agent + 6% cement" reduces the heavy metal leaching rate by 92%, but the 7-day compressive strength is only 1.8 MPa, the harmful substance residue is high and the strength is weak; coal gangue treatment: using only 0.4% curing agent to achieve radioactivity compliance, the permeable brick strength is ≥12 MPa, the safety meets the standard but the engineering performance is conservative; core problem: the harmful substance treatment efficiency is insufficient and the material strength does not meet the ideal standard.
[0116] Example 2 is a comprehensive optimization (short-term improvement), including: lithium slag: under the same formula, the harmful substance treatment efficiency is significantly improved - fluorine is reduced to 4.01 times, beryllium / manganese reaches 1500 times / 2200 times respectively (an increase of 25%-45% compared with Example 1), and the compressive strength jumps to ≥24 MPa, proving the potential of the formula; phosphogypsum: the leaching rate is reduced by 96%, and the 7-day compressive strength is increased to 2.0 MPa, and the short-term safety and strength are improved simultaneously; coal gangue: the strength of permeable bricks breaks through to ≥14 MPa (+16.7%), and the engineering applicability is enhanced; key progress: both environmental protection and engineering indicators are improved, but due to the lack of long-term performance data, the durability of phosphogypsum is questionable.
[0117] Example 3: Comprehensive breakthroughs (optimal performance), including: Lithium slag: Pest control reached its peak - fluorine (4.14 times), thallium (3.23 times), beryllium (1586 times), and manganese (2375 times) all reached the highest values among the four tables, and compressive strength ≥22 MPa (maintained at a high level); Phosphogypsum: The solution was adjusted to "0.3L / m³ curing agent + 6% cement", achieving two major breakthroughs: ① A 98% reduction in leaching rate (optimal among the four examples); ② The first-ever 28-day compressive strength (5.0-6.3 MPa) was provided, far exceeding the 7-day strength (1.8-2.0 MPa) of other tables, demonstrating long-term stability; Coal gangue: Strength ≥13 MPa, slightly lower than Example 2 but maintaining radioactivity compliance; Core advantages: Comprehensively leading in hazardous material treatment efficiency (reduction in lithium slag pollutants, 98% leaching rate for phosphogypsum); the only one to provide long-term strength data (28-day strength of phosphogypsum), significantly improving project reliability; and the optimal balance between environmental protection and long-term performance.
[0118] Example 4: Performance fluctuation (strength priority, environmental protection concession), including: lithium residue: compressive strength creates a new high (≥25 MPa), but harmful substance treatment efficiency falls - fluorine (3.80 times), beryllium (1406 times), manganese (2015 times) are lower than Example 2, Example 3, sacrificing environmental protection effect for strength improvement; phosphogypsum: leaching rate decreased by 94% (weaker than 96% in Table 2, 98% in Table 3), 7-day compressive strength 1.9 MPa, key indicators retrogress; coal gangue: strength regression ≥13 MPa, radioactivity continues to meet standards; prominent contradiction: lithium residue compressive strength is optimized to 25 MPa, but phosphogypsum environmental protection and engineering performance are inferior to Example 2, Example 3, overall performance is uneven.
[0119] In summary, Example 3 has the best performance, the specific reasons are as follows:
[0120] Long-term strength (28 days) data of phosphogypsum - core indicator of engineering application;
[0121] Overall leading harmful substance treatment efficiency (especially phosphogypsum 98% and lithium residue Be / Mn).
[0122] Example 3 has 98% leaching rate reduction of phosphogypsum + 28-day strength data as the core advantage, combined with overall leading harmful substance treatment of lithium residue, becomes the only solution that takes into account high environmental protection standards and long-term engineering reliability. Although the lithium residue in Example 4 has higher strength, its environmental protection indicators have regressed and the performance of phosphogypsum has declined, and the overall value is not as good as Example 3.
[0123] From Figure 1 it can be known that SEM shooting and analysis of the solidifying agent from different angles show that the solidifying agent has a hollow tubular structure. Its particles are uniformly dispersed, which should be the emulsification effect of fatty alcohol polyoxyethylene ether.
[0124] From Figure 2 it can be known that it has ester group stretching vibration at 1700 cm -1 around wave number, reflecting the existence of ester group in polyglycerol fatty acid ester; 3300 cm -1 has a wide peak reflecting the association state of PVA hydroxyl group 1470 cm -1 nearby doublet reflects the bending vibration of methylene in emulsified paraffin.
[0125] From Figure 3 and Figure 4 it can be known that Figure 3 and Figure 4 are the hydrogen spectrum and carbon spectrum of the solidifying agent respectively, and the strong peaks of the two figures reflect the existence of ester group in glycerol fatty acid ester, which, combined with Figure 2 proves that the emulsification reaction is successful.
[0126] Figure 5Diagram of the solid waste treatment mechanism of lithium slag using a solidifying agent. Carboxylic acid captures ions, dissociating into carboxyl ions that selectively complex to form insoluble salts through coordination bonds, immobilizing soluble heavy metals and blocking their migration. Polyglycerol esters are halogenated to form hydrophobic halogenated polyglycerol esters, which wrap around solid waste particles to form a hydrophobic layer, blocking water molecule penetration and inhibiting pollutant leaching. Organic components in the solid waste react with halogens at high temperatures to form covalent carbides. The high-hardness structure permanently solidifies heavy metals or generates volatile halides, allowing pollutants to be removed through gas-solid separation. In the emulsified paraffin system, the paraffin wax emulsion seals thallium ions within the hydrophobic droplets, completely blocking their release.
[0127] Table 5 is a summary of the pH performance test results of the untreated lithium slag and the test results of fluoride, beryllium, thallium, manganese, etc. when the curing agent was used to treat the sample 1# and the sample 2#, respectively.
[0128] Table 5 Summary of test results of curing agent on different samples
[0129]
[0130] Tables 6 and 7 are respectively a summary of the test results of phosphogypsum mix strength and a summary of the test results of on-site compressive strength and thickness, as shown in Tables 6 and 7 below.
[0131] Tables 8 and 9 are the summary tables of on-site density data and on-site moisture content data, respectively. Details are shown in Tables 8 and 9 below.
[0132]
[0133]
[0134]
[0135] On-site 700m 2 The representative number was tested and the average maximum dry density was 1.86g / cm 3 The average compaction coefficient is 96%, and the on-site inspection report is qualified.
[0136] Table 10 is a summary of the test method and test results of the leaching solution of the unfired brick sample 2#, as shown in Table 10.
[0137]
[0138] In summary, based on the chemical behavior characteristics of heavy metal ions in solid waste, this invention constructs a multifunctional chelating system through molecular design, and innovatively develops a method for preparing a water-resistant and pressure-resistant energetic curing agent through organic polymerization. This method can achieve the following breakthroughs through a four-stage precise control process (esterification → neutralization → emulsification → paraffin integration):
[0139] Innovation in chelation mechanism: The core skeleton is the acetylated product generated by the esterification reaction of polyglycerol fatty acid ester and acetic acid. Its electron-rich carboxyl group forms a stable coordination bond with heavy metal ions (such as thallium and beryllium); the ether bond of fatty alcohol polyoxyethylene ether cooperates with the phenolic hydroxyl group of sodium lignin sulfonate to capture fluoride and manganese ions through hydrogen bond-coordination dual-mode action; the long alkane chain of emulsified paraffin directionally wraps the chelate to form a hydrophobic barrier, completely blocking the leaching path of harmful substances.
[0140] The present invention fundamentally solves the difficult problems of heavy metal ion migration pollution and insufficient resource utilization intensity in solid waste (lithium slag, coal gangue, phosphogypsum, etc.). The constructed "chelation-encapsulation-hydrophobic" triple stabilization mechanism, combined with a four-stage organic polymerization process, provides technical support for scalable application in the construction of "zero-waste cities".
[0141] In addition, the technology of this invention has passed third-party testing and certification (report number: FX2024-444-1), and has been successfully applied in projects such as the Yan'an coal gangue roadbed and Anhui phosphogypsum consolidation body, providing an efficient, economical and green industrialization path for solid waste resource utilization.
[0142] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any modifications or substitutions that can be easily conceived by a person skilled in the art within the technical scope disclosed in the present invention should be included in the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be based on the scope of protection of the claims.
Claims
1. A water-resistant and pressure-resistant solid waste solidification material, characterized in that: Prepared by including the following components in percentage by weight: Polyglycerol fatty acid ester 5-15%, acetic acid 10-20%, fatty alcohol polyoxyethylene ether 35-50%, polyvinyl alcohol 3-5%, sodium lignin sulfonate 3-5%, emulsified paraffin 15-30%.
2. The water-resistant and pressure-resistant solid waste solidification material according to claim 1, characterized in that: Prepared by including the following components in percentage by weight: Polyglycerol fatty acid ester 5%, acetic acid 20%, fatty alcohol polyoxyethylene ether 45%, polyvinyl alcohol 3%, sodium lignin sulfonate 4%, emulsified paraffin 23%.
3. A method for preparing the water-resistant and pressure-resistant solid waste solidification material according to claim 1, characterized in that: include: Allowing polyglycerol fatty acid ester and acetic acid to undergo an esterification reaction, and controlling the acid value of the solution within a preset acid value threshold range during the reaction, thereby obtaining a first reaction solution; Slowly adding an alkaline solution dropwise to the first reaction solution to adjust the pH of the solution to alkaline, thereby obtaining a second reaction solution; sequentially adding fatty alcohol polyoxyethylene ether, polyvinyl alcohol solution, and sodium lignin sulfonate solution to the second reaction solution, and reacting to obtain a mixed solution; After the mixed liquid is cooled to a preset temperature range, emulsified paraffin is added to react, and then cooled to obtain a water-resistant and pressure-resistant energy-empowered solid waste solidification material.
4. The method for preparing the water-resistant and pressure-resistant solid waste solidification material according to claim 3, characterized in that: The temperature range of the esterification reaction is 80-110°C, and the reaction time is 1-3 hours.
5. The method for preparing the water-resistant and pressure-resistant solid waste solidification material according to claim 3, characterized in that: The preset acid value threshold range is 35~50 mg KOH / g.
6. The method for preparing the water-resistant and pressure-resistant solid waste solidification material according to claim 3, characterized in that: The alkaline solution includes one or more of sodium bicarbonate and sodium hydroxide.
7. The method for preparing the water-resistant and pressure-resistant solid waste solidification material according to claim 3, characterized in that: The reaction temperature of the fatty alcohol polyoxyethylene ether is 65-75°C, and the reaction time is 20 min.
8. The method for preparing the water-resistant and pressure-resistant solid waste solidification material according to claim 3, characterized in that: The pre-dissolving temperature of the polyvinyl alcohol solution is 85°C, and the solid-liquid ratio is 1:15; the pre-dissolving temperature of the sodium lignin sulfonate solution is 40-50°C, and the solid-liquid ratio is 1:
5.
9. Use of the water-resistant and pressure-resistant solid waste solidification material according to any one of claims 1-2 or the water-resistant and pressure-resistant solid waste solidification material prepared by the method according to any one of claims 3-8 in fire-free building materials.
10. A fired brick, characterized in that: The invention comprises the water-resistant and pressure-resistant solid waste solidification material according to any one of claims 1-2 or the water-resistant and pressure-resistant solid waste solidification material prepared by the method according to any one of claims 3-8.
Citation Information
Patent Citations
Modified sodium lignin sulfonate chelating agent containing phosphonic acid group and preparation method thereof
CN104558633A
Silt hardening agent and preparation method and application method thereof
CN107522436A
Curing agent for cement or soft soil and roadbed material formed by curing agent
CN113429151A
Organic-inorganic composite material for stabilizing treatment of heavy metal waste residues and preparation method of organic-inorganic composite material
CN113441513A
Soil stabilizer and preparation method thereof
CN115074134A